A STUDY ON REVERSE MIGRATION OF HUMAN RESOURCES: A STUDY OF UTTARAKHAND STATE - Seema Parveen, Dr Pradeep Mamgain (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The idea of national lock-down and home quarantine is the key to fighting against the Covid-19 pandemic is gaining currency among global political leaders. National lock-down has required dramatic changes in the India of work – a shift of workplaces into virtual mode, or working from home those workforce who are based on monthly based salary and have sufficient resources in home but apart from this there is a question of daily wage bases informal human resources . The corona virus pandemic has a mountain problem to the world but to some extent it’s had positive impact on reverse migration in Himalayan state of Uttarakhand. Due to the Covid-19 nation-wide lock-down has resulted people who employed with the private and informal sector returned to their native villages in the state in the past few days during the lockdown. In this paper we study the beneficial and detrimental impact of reverse migration during national lockdown on rural areas of Uttarakhand. Also provide some important suggestion have been proposed toretain its youth permanently through the effective implementation of government plan and policies.